Spotlight on avian pathology: Marek's disease. Issue 5 (3rd September 2018) - Nair, Venugopal
ABSTRACT: Marek's disease (MD), characterised by rapid-onset lymphoid tumours, immunosuppression and paralysis, is one of the most widespread economically important diseases of poultry world-wide. Caused by the highly contagious Marek's disease virus, control of MD is mainly achieved through vaccination with live attenuated vaccines, although improvements in genetic resistance have also been an important component of disease control. Despite the overall success of the vaccination policy in controlling MD in the last 40 years, continuous evolution of virulence and emergence of hypervirulent pathotypes remains the major challenge for sustainable control of this disease.